Cytochrome P450 Epoxygenase-Dependent Activation of TRPV4 Channel Participates in Enhanced Serotonin-Induced Pulmonary Vasoconstriction in Chronic Hypoxic Pulmonary Hypertension - Yang Xia; Lexin Xia; Zhou Jin; Rui Jin; Omkar Paudel; James S. K. Sham (Analytical Cellular Pathology)
Transient receptor potential vanilloid 4 (TRPV4) is a multi-functional non-selective channel expressed in pulmonary vasculatures. TRPV4 contributes to serotonin- (5-HT-) induced pulmonary vasoconstriction and is responsible in part for the enhanced 5-HT response in pulmonary arteries (PAs) of chronic hypoxia mice. Epoxyeicosatrienoic acid (EET) is an endogenous agonist of TRPV4 and is known to regulate vasoreactivity. The levels of EETs, the expression of cytochrome P450 (CYP) epoxygenase for EET production, and epoxide hydrolase for EET degradation are altered by chronic hypoxia. Here, we examined the role of EET-dependent TRPV4 activation in the 5-HT-mediated PA contraction. In PAs of normoxic mice, inhibition of TRPV4 with a specific inhibitor HC-067047 caused a decrease in the sensitivity of 5-HT-induced PA contraction without affecting the maximal contractile response. Application of the cytochrome P450 epoxygenase inhibitor MS-PPOH had no effect on the vasoreactivity to 5-HT. In contrast, inhibition of CYP epoxygenase or TRPV4 both attenuated the 5-HT-elicited maximal contraction to a comparable level in PAs of chronic hypoxic mice. Moreover, the inhibitory effect of MS-PPOH on the 5-HT-induced contraction was obliterated in PAs of chronic hypoxic trpv4-/- mice. These results suggest that TRPV4 contributes to the enhanced 5-HT-induced vasoconstriction in chronic hypoxic PAs, in part via the CYP-EET-TRPV4 pathway. Our results further support the notion that manipulation of TRPV4 function may offer a novel therapeutic strategy for the treatment of hypoxia-related pulmonary hypertension.